The impact of the type of nodal assessment on prognosis in patients with high-intermediate and high-risk ESMO/ESGO/ESTRO group endometrial cancer. A multicenter Italian study. Issue 10 (October 2018) - Buda, Alessandro; Restaino, Stefano; Di Martino, Giampaolo; De Ponti, Elena; Monterossi, Giorgia; Dinoi, Giorgia; Magni, Sonia; Quagliozzi, Lorena; Dell'Orto, Federica; Ciccarone, Francesca; Lamanna, Maria; Scambia, Giovanni; et al.
Abstract: Objectives: The majority of endometrial cancers (EC) are discovered while the disease is confined to the uterine body. The presence of lymph nodes metastases impairs the prognosis. In this study, we evaluated the possible impact on survival of sentinel lymph node (SLN) mapping algorithm and selective lymphadenectomy (LD) in early stage EC, according to the ESMO-ESGO-ESTRO risk subgroup classification. Methods: We retrospectively analyzed the database from two collaborative institutions including women with high-intermediate (HI) and high-risk (HR) ESMO/ESGO/ESTRO groups that underwent surgical staging with either SLN mapping, or selective LD. Results: Two-hundred and sixty-six women were overall identified, 121 in HI and 145 in HR group, respectively. LD was performed in 139 patients (52.5%), whereas SLN mapping algorithm in 61 patients (23%). Sixty-six patients in Rome center were not staged (24.8%). Aortic dissection was performed in 29 women (10.9%). The 3-year comparison did not show a significant difference between strategy adopted for nodal staging (SLN mapping, LD, and SLN + LD) on both disease-free survival [HR: 0.82; 95% CI 0.53–1.28; p = 0.390], and overall survival [HR: 0.78; 95% CI 0.47–1.31; p = 0.355]. Conclusions: In this study focused on women in the HI and HR groups we did not find difference in the 3-years DFS and OS when comparing the SLN strategy with selective lymphadenectomy, or the SLN algorithm. The SLN strategy did not seem to not compromise the prognosis of high risk patients.